Can media change the way you think? The impact of foreign media cultural exposure on creativity and cultural intelligence - Lee, Hui Min (2018)
With globalisation, many cultures have spread their influence across the globe via mass media, changing the world rapidly. In a bid to understand the impacts of such a progression, this research examines the outcomes of foreign media cultural exposure on creativity and cultural intelligence together with the role of stereotyping as a mediator in this relationship. It is hypothesized that cultural exposure will lead to increased creativity and cultural intelligence, and that this relationship will be mediated via reduced stereotyping. While the mediation relationship with stereotyping was found to be insignificant, there was some evidence that cultural exposure did positively impact creativity and reduced stereotyping independently. Taken together, this study sheds light on the possible implications of cultural exposure via media, along with suggestions for future directions.